Taliban : the power of militant Islam in Afghanistan and beyond - Rashid, Ahmed (I.B. Tauris, 2010)
The American bombing of terrorist bases in Afghanistan under the protection of the Islamic fundamentalist Taliban movement has brought the Taliban into sharp focus as the most radical and extreme Islamic movement in the world today. Little is known about the Taliban because of the deep secrecy that surrounds their political movement, their leaders and their aims._x000D__x000D_The geo-strategic implications of the Taliban are already creating severe instability in Russia, Iran and the five Central Asian republics where the Taliban have become a major player in the new Great Game, as Western cou.